DISEASE OF THE FEMALE REPRODUCTIVE SYSTEM, WHICH MANIFESTS ITSELF WITH DIABETES MELLITUS TYPE 2 - Rabbimova Nilufar Ulugbekovna; Abduxalimova Yulduz Jaxongirovna (TADQIQOTLAR.UZ, 2024)
Relevance: Epidemiological studies have shown that cancer of the female reproductive system, including endometrial and ovarian cancers, is more common in people with diabetes. One of the meta-analyses showed a statistically significant association of DM2 with the risk of endometrial cancer (total relative risk (HR) 2.10; 95% confidence interval (CI) 1.75-2.53). This meta-analysis also talks about the relationship between DM1 and endometrial cancer (total HR 3.15; 95% CI 1.07-9.29). It should be noted that many studies provide evidence in favor of the fact that the incidence of cancer of the ovaries, esophagus, endometrium, vulva and vagina, thyroid gland is higher among women with DM1. On the other hand, patients with DM1 have a lower risk of developing breast cancer, melanoma and Hodgkin's lymphoma. Cells of most types of malignant neoplasms predominantly express the type 1 glucose transporter, which has a high affinity for glucose. It is also worth mentioning the Warburg effect, in which glucose in tumor cells follows an energetically inefficient glycolysis pathway with a high level of lactate production. Increased glycolysis in tumor cells provides the materials necessary for the synthesis of nucleotides, amino acids and lipids. In addition, hyperglycemia is responsible for DNA damage, which is the first stage of oncogenesis. For endometrial cancer, it has been suggested that in precancerous conditions or an existing tumor disease, endometrial cells, as well as microenvironment cells, can use excess glucose to stimulate anabolic pathways and disease progression. The genetic features of endometrial cancer indicate that most of these tumors already have a predisposition to increased glucose metabolism due to loss of expression. In DM2, insulin resistance leads to the development of compensatory hyperinsulinemia. High concentration of insulin in the blood plays one of the key roles in the pathogenesis of malignant neoplasms, which has been demonstrated in numerous studies both in vitro and in vivo.